Upgraded Giant Metrewave Radio Telescope timing of NGC 1851A: a possible millisecond pulsar − neutron star system. Issue 3 (25th September 2019) - Ridolfi, A; Freire, P C C; Gupta, Y; Ransom, S M
ABSTRACT: In this work, we present the results of 1 yr of upgraded Giant Metrewave Radio Telescope timing measurements of PSR J0514−4002A, a 4.99-ms pulsar in a 18.8-d eccentric (e = 0.89 ) orbit with a massive companion located in the globular cluster NGC 1851. Combining these data with earlier Green Bank Telescope data, we greatly improve the precision of the rate of advance of periastron, ω = 0.0129592(16) yr^-1 which, assuming the validity of general relativity, results in a much refined measurement of the total mass of the binary, M_tot = 2.4730(6) M_ . Additionally, we measure the Einstein delay parameter, γ, something that has never been done for any binary system with an orbital period larger than 10 h. The measured value, γ = 0.0216(9) s, is by far the largest for any binary pulsar. Furthermore, we measure the proper motion of the system (μ _α = 5.19(22) and μ _δ = -0.56(25) mas yr^-1 ), which is not only important for analysing its motion in the cluster, but is also essential for a proper interpretation of γ, given the latter parameter's correlation with the variation of the projected semimajor axis. The measurements of γ and the proper motion enable a separation of the system component masses: we obtain a pulsar mass of M_p = 1.25^+0.05_-0.06 M_ and a companion mass of M_c = 1.22^+0.06_-0.05 M_ . This raises the possibility that the companion is also a neutron star. Searches for radio pulsations from the companion have thus far been unsuccessful; hence, we cannot confirm the latter hypothesis. The low mass of this millisecond pulsar – one of the lowest ever measured for such objects – clearly indicates that the recycling process can be achieved with a relatively small amount of mass transfer.